Gum chewing while walking increases walking distance and energy expenditure: A randomized, single-blind, controlled, cross-over study - Yuka Hamada; Chihiro Nagayama; Kyoko Fujihira; Yusei Tataka; Ayano Hiratsu; Kayoko Kamemoto; Kanako Shimo; Susumu Kanno; Kenji Osawa; Masashi Miyashita (Elsevier, 2021)
Background/objective: Gum chewing while walking increases walking distance and energy expenditure in middle-aged male and female individuals. This study aimed to examine the effects of gum chewing while walking on walking distance and energy metabolism in male and female individuals of various age groups. Methods: Fifty participants (25 male and 25 female individuals) aged 22-69 years completed two trials in a random order. In the gum trial, participants walked at a natural pace for 15 min while chewing two gum pellets (1.5 g, 3 kcal per pellet) following a 50-min rest period. In the tablet trial, participants rested for 50 min before walking, and the participants then walked at a natural pace for 15 min after ingesting two pellets of tablet containing the same ingredients with the exception of the gum base. The walking distance, step count, walking speed, stride, heart rate, energy expenditure, and respiratory exchange ratio were measured. Results: Walking distance, step count, walking speed, heart rate, and energy expenditure during walking were significantly higher in the gum trial than in the tablet trial. In participants aged ≥40 years, walking distance, walking speed, stride, heart rate, and energy expenditure during walking were significantly increased during the gum trial compared with those during the tablet trial. Conclusion: The study findings demonstrated that gum chewing while walking increased walking distance and energy expenditure in both male and female individuals.